Respuesta :

Answer:

x² + 9x + 8 = (x + 1)(x + 8)

x² + 9x + 8 = (x + 8)(x + 1)

Step-by-step explanation:

* Lets explain how to factorize the polynomial using the pattern

- The form of the quadratic polynomial is x² + px + q, where p is the

  coefficient of x and q is the numerical term

∵ x² + (a + b)x + (ab) = (x + a)(x + b)

- From the formula above the coefficient of x is the sum of the two

 factors a and b

∴ p = a + b and q = ab

- That means p is the sum of two numbers and q is the product of

  the same numbers

* Lets solve the problem

∵ x² + 9x + 8 is a quadratic polynomial

∵ x² + px + q is the form of quadratic polynomial

∴ p = 9 and q = 8

∵ p = a + b and q = ab

∴ a + b = 9 ⇒ (1)

∴ ab = 8 ⇒ (2)

- We must to find two numbers their product is 8 and their sum is 9

∵ The possibility of 8 as a product of two numbers is:

   2 × 4 OR 1 × 8

∵ The sum of 1 + 8 = 9

∴ The value of a and b are 1 and 8

- It does't matter which of them = 1 or which of them = 8

∴ x² + (a + b)x + ab = x² + (1 + 8)x + (1)(9)

∵ x² + (a + b)x + (ab) = (x + a)(x + b)

∴ x² + (1 + 8)x + (1)(9) = (x + 1)(x + 8)

∴ x² + 9x + 8 = (x + 1)(x + 8)

- OR

∴ x² + 9x + 8 = (x + 8)(x + 1)